2021
DOI: 10.1101/2021.01.30.428927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geography, not host identity, shapes bacterial community in reindeer lichens

Abstract: Background and AimsTremendous progress have been recently achieved in host-microbe research, however, there is still a surprising lack of knowledge in many taxa. Despite its dominance and crucial role in boreal forest, reindeer lichens have until now received little attention. We characterize, for the first time, the bacterial community of four species of reindeer lichens from Eastern North America’s boreal forests. We analysed the effect of two factors (host-identity and geography) in the bacterial community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 112 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, bacterial communities dominated by Acidobacteria (followed by Alphaproteobacteria, Gammaproteobacteria, Actinobacteria, Planctomycetes, and Verrucomicrobia) have been previously described for Cladonia thalli based on amplicon sequencing analysis [ 97 ]. Recent studies using high-throughput DNA sequencing of microbial communities have also confirmed the predominance of Alphaproteobacteria among the non-phototrophic bacteria in many other lichens [ 12 , 74 , 75 , 83 , 86 , 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Nevertheless, bacterial communities dominated by Acidobacteria (followed by Alphaproteobacteria, Gammaproteobacteria, Actinobacteria, Planctomycetes, and Verrucomicrobia) have been previously described for Cladonia thalli based on amplicon sequencing analysis [ 97 ]. Recent studies using high-throughput DNA sequencing of microbial communities have also confirmed the predominance of Alphaproteobacteria among the non-phototrophic bacteria in many other lichens [ 12 , 74 , 75 , 83 , 86 , 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 96%
“…The lichenised fungal genus Cladonia has an almost cosmopolitan distribution and has been the target of many taxonomic and ecological studies over the years [ 29 ]. Recently, investigations on lichen microbial communities have expanded our knowledge of the diversity of eukaryotes and prokaryotes living in the lichen thalli [ 2 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. Here, we used OTU amplicon sequencing of bacteria (16S rRNA V3-V4 gene region) and fungi/microalgae (ITS2 region) to observe the diversity of microbial communities present in the thalli of six Cladonia specimens collected from boreal forest and urban area environments in Southern Finland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations